KONTRIBUSI PONDOK PESANTREN DALAM PENGEMBANGAN PENDIDIKAN MASYARAKAT DI PESANTREN ROUDLOTUL MUTA’ALLIMIN DESA TAMPO KECAMATAN CLURING KABUPATEN BANYUWANGI - Hasim Ashari (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2019)
Abstract The ability of pesantren to always develop community education is proof of the existence of these institutions in the midst of a society that continues to experience change. Islamic boarding schools are able to mobilize resources, both energy and funds, to be able to play an active role as a stronghold against various cultures that have a negative impact. This fact also shows that pesantren are educational institutions that have the strength to survive in the midst of the community. The pesantren is also still able to show its contribution in the development of community education today.